Retention & Graduation Report - Office of Assessment (Kansas State University. K-State First., 2014)
Student Retention and Graduation Rates for K-State First Students and Non-K-State First Students
Keywords: Retention; Enrollment; GPA; Learning communities; First-year seminars; Fliers (printed matter)